Studi Deskriptif Program Suplementasi Tablet Besi Pada Ibu Hamil Di Puskesmas Kalijudan Kota Surabaya - Nadia Kenyo Peni Dewantoro; Lailatul Muniroh (Amerta Nutrition, 2017)
Background: Supplementation of iron tablet is one of the government program that aims to decrease prevalence of-anemia on pregnant-women. The average corevage of iron tablet program on pregnant women in the work area of-Distric-Health-Government of Surabaya over past three years has decrease. If coverage value is reviewed by each public-health-center, there are some public-health-center whose coverage is increased one of-them is Kalijudan Public-Health-Center but is not followed by a-decrease number of anemia in pregnant women. Objectives: This research aims was to describe the implementation of-iron tablet program in Kalijudan-Public Health-Center and used system approach. Methods: The type of- this research was qualitative and involved 8-health workers and 15 pregnant-women as informants. Determination of informant involvement used purposive sampling and accidental sampling technic. Results: Health workers that involved came from various profession and were sufficient in terms quantity and qualification. The funds used for iron tablet purchases came from National-Health-Insurance. The hemoglobin examination tool was hematology analyzer and operated by laboratory worker. The availability of-iron tablets was deficience. The process stage, iron tablets planning was done once per year and its procurement followed schedule from Distric-Health-Government. The number of tablets was given to pregnant-women in a-single visit followed a-control schedule or 15-tablets. The monitoring of iron tablet consumption compliance was done with simple interview. Special organizing of-health workers for program did not yet exist. The output stage, recording coverage percentages were performed at the end of each year. The outcome stage, prevalence of-anemia in pregnant-women could not be known.Conclusion: The implementation of-program can be said not run well, because there are still some obstacles.ABSTRAK Latar belakang: Suplementai Tablet Besi merupakan salah satu program pemerintah dalam upaya menurunkan prevalensi anemia pada ibu hamil. Nilai rata-rata cakupan pemberian tablet besi pada ibu hamil di wilayah kerja Dinas-Kesehatan-Kota Surabaya selama tiga tahun terakhir mengalami penurunan. Bila nilai cakupan ditinjau pada tiap puskesmas, maka terdapat beberapa puskesmas yang cakupannya mengalami peningkatan salah satunya yakni Puskesmas Kalijudan tetapi belum diikuti dengan penurunan prevalensi anemia ibu hamil.Tujuan: Penelitian ini bertujuan untuk mengetahui pelaksanaan program suplementasi tablet besi di Puskesmas Kalijudan dengan menggunakan pendekatan sistem.Metode: Jenis penelitian ini ialah kualitatif yang melibatkan 8 orang tenaga kesehatan dan 15 orang ibu hamil sebagai informan. Penentuan keterlibatan informan menggunakan teknik purposive sampling dan accidental sampling.Hasil: Tahap input, tenaga kesehatan dalam program berasal dari berbagai profesi dan sudah cukup dari segi jumlah dan kualifikasi. Dana pembelian tablet berasal dari Jaminan Kesehatan Nasional. Alat periksa hemoglobin adalah hematology analyzer dan dioperasikan oleh petugas laboratorium. Ketersediaan tablet besi mengalami kekurangan. Segi tahap proses, perencanaan tablet besi dilakukan satu tahun sekali dan pengadaan mengikuti jadwal Dinas-Kesehatan-Kota-Surabaya. Banyaknya tablet yang diberi pada ibu hamil dalam satu kali kunjungan mengikuti jadwal kontrol atau 15 tablet. Monitoring kepatuhan konsumsi tablet dilakukan dengan wawancara sederhana. Pengorganisasian tenaga kesehatan khusus pelaksana program tablet besi belum ada. Segi tahap output, pencatatan persentase cakupan hanya dilakukan setiap akhir tahun. Segi tahap outcome, prevalensi anemia ibu hamil tidak dapat diketahui.Kesimpulan: Pelaksanaan program suplementasi tablet besi dapat dikatakan belum berjalan dengan baik, dikarenakan masih terdapat kendala di beberapa tahapan.